2012
DOI: 10.1002/mrm.24443
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensionally encoded magnetic resonance imaging

Abstract: Magnetic resonance imaging typically achieves spatial encoding by measuring the projection of a q-dimensional object over q-dimensional spatial bases created by linear spatial encoding magnetic fields (SEMs). Recently, imaging strategies using nonlinear SEMs have demonstrated potential advantages for reconstructing images with higher spatiotemporal resolution and reducing peripheral nerve stimulation. In practice, nonlinear SEMs and linear SEMs can be used jointly to further improve the image reconstruction pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…The encoding fields from previous PatLoc and O-space implementations are thus theoretically related to each other by using different SEMs generated from a system of surface gradient elements with a circumferential arrangement. Although we did not explore including O-ring SEM for PatLoc imaging here, some preliminary studies have suggested that different SEMs, including O-ring, M1/M2, and L1/L2 SEMs, can be used jointly to improve the spatial encoding efficiency (19). We will pursue this research topic in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…The encoding fields from previous PatLoc and O-space implementations are thus theoretically related to each other by using different SEMs generated from a system of surface gradient elements with a circumferential arrangement. Although we did not explore including O-ring SEM for PatLoc imaging here, some preliminary studies have suggested that different SEMs, including O-ring, M1/M2, and L1/L2 SEMs, can be used jointly to improve the spatial encoding efficiency (19). We will pursue this research topic in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…But if we simulate radial imaging with 16, 32 and 64 points per echo, the rank of each encoding matrix E is 954, 1609 and 2461, respectively. More efficient encoding in MRI is possible, since MR images typically represent rank deficient matrices [29-30], and a higher rank encoding matrix E generally denotes a more efficient encoding [19, 31-32]. Therefore, the rank of the encoding matrices suggests that the proposed strategy, parallel imaging with O-Space acquisitions, is superior to parallel imaging with radial encoding, and the difference is increasingly pronounced at higher resolution readouts.…”
Section: Theorymentioning
confidence: 99%
“…O-Space imaging [6-7] was the first sequence explicitly designed to improve highly undersampled parallel imaging with nonlinear gradients, though many other methods have since been studied. These include Patloc Imaging [1], Null Space imaging [5], O-Space TSE imaging [8-10], Single Echo MRI [11], FRONSAC imaging [12-15], 4D-RIO [16], EPI-PatLoc [17], CS O-Space [18], Multi-Dimensional Encoding [19] and others [20-23]. …”
Section: Introductionmentioning
confidence: 99%
“…For instance, linear imaging gradients create a constant frequency encoding across the image weighted by the coil sensitivity profile . Developments in the application of nonlinear SEM fields for parallel imaging have focused on reducing peripheral nerve stimulation , perfecting local k‐space coverage , signal to noise (SNR) optimization through frame analysis , and algebraic determination of arbitrary encoding fields such as null space imaging (NSI) . Local k‐space analysis, which plots the k‐space from the spatial derivative of encoded phase, k(t)=φ(x,t), provides an intuitive examination of the spatially‐varying nature of nonlinear acquisitions albeit without accounting for spatial localization from the receivers .…”
Section: Introductionmentioning
confidence: 99%